A pharmacological strategy to recapitulate exercise-induced antitumoral immunity. (December 2022) - Rébillard, Amélie; Nunès, Jacques A.; Carrier, Alice
Abstract : The antitumor activity of exercise by means of enhanced immune activation is documented, but better identification of the underlying mechanisms is required to develop new therapeutic strategies. Recent work from the Dr Bar-Sagi group reveals that exercise engages IL-15 signaling and pharmacological activation of the IL-15/IL-15R axis mimics the exercise-driven immune cell-mediated cytotoxicity in pancreatic cancer.